Geochemistry, carbon isotope ratio and radiocarbon ages of sediment core GIK1093-2 from Bornholm Basin, Baltic Sea - Erwin Suess; Helmut Erlenkeuser (PANGAEA, 1975)
Concentrations of Cd, Pb, Zn, Cu, Co, Ni, Fe, and Al203, water content, the amounts of organic carbon, the ratio of 13C/12C and the 14C-activity of the organic fraction were determined with sediment depth from a 34 cm long box-core from the Bornholm Basin (Baltic Sea). The average sedimentation rate was 2.4 mm/yr. The upper portion of the core contained increasing amounts of 14C-inactive organic carbon, and above 3 cm depth, man-made 14C from atomic bomb tests. The concentrations of the heavy metals Cd, Pb, Zn, and Cu increase strongly towards the surface, while other metals, as Fe, Ni and Co remain almost unchanged. This phenomenon is attributed to anthropogenic influences. A comparison of the Kieler Bucht, the Bornholm and the Gotland Basins shows that today the anthropogenic addition of Zn is about 100 mg/m**2 yr in all three basins. The beginning of this excess of Zn, however, is delayed by about 20 years in, the Bornholm Basin and by about 40 years in the Gotland Basin. It is suggested that SW-NE transport of these anthropogenically mobilized metals may be related to periodic bottom water renewal in the Baltic Sea sedimentary basins.
Supplement to: Suess, E; Erlenkeuser, H (1975): History of metal pollution and carbon input in Baltic Sea sediments. Meyniana, 27, 63-75, https://doi.org/10.2312/meyniana.1975.27.63